Gut microbiota composition in patients with advanced malignancies experiencing immune-related adverse events - Xinyu Liu; Xinyu Liu; Hao Tang; Qingyang Zhou; Yanlin Zeng; Yanlin Zeng; Bo Lu; Dan Chen; Yue Li; Jiaming Qian; Minjiang Chen; Jing Zhao; et al. (Frontiers in Immunology, 2023)
IntroductionThe gut microbiota is implicated in the occurrence and severity of immune-related adverse events (irAEs), but the role it plays as well as its causal relationship with irAEs has yet to be established.MethodsFrom May 2020 to August 2021, 93 fecal samples were prospectively collected from 37 patients with advanced thoracic cancers treated with anti-PD-1 therapy, and 61 samples were collected from 33 patients with various cancers developing different irAEs. 16S rDNA amplicon sequencing was performed. Antibiotic-treated mice underwent fecal microbiota transplantation (FMT) with samples from patients with and without colitic irAEs.ResultsMicrobiota composition was significantly different in patients with and without irAEs (P=0.001) and with and without colitic-type irAEs (P=0.003). Bifidobacterium, Faecalibacterium, and Agathobacter were less abundant and Erysipelatoclostridium more abundant in irAE patients, while Bacteroides and Bifidobacterium were less abundant and Enterococcus more abundant in colitis-type irAE patients. Major butyrate-producing bacteria were also less abundant in patients with irAEs than those without (P=0.007) and in colitic vs. non-colitic irAE patients (P=0.018). An irAE prediction model had an AUC of 86.4% in training and 91.7% in testing. Immune-related colitis was more common in colitic-irAE-FMT (3/9) than non-irAE-FMT mice (0/9).ConclusionsThe gut microbiota is important in dictating irAE occurrence and type, especially for immune-related colitis, possibly by modulating metabolic pathways.